2019
DOI: 10.1016/j.ijpsycho.2018.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing the constituent oscillatory dynamics underlying mismatch negativity generation in schizophrenia: Distinct relationships to clinical and cognitive functioning

Abstract: Abnormalities in early auditory information processing (EAIP) contribute to higher-order deficits in cognition and psychosocial functioning in schizophrenia. A passive auditory oddball paradigm is commonly used to evoke event-related potential (ERP) measures of EAIP reflecting auditory sensory registration and deviance detection, including mismatch negativity (MMN) and P3a responses. MMN and P3a have been extensively studied in healthy subjects and neuropsychiatric patient populations and are increasingly used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
(73 reference statements)
1
13
0
Order By: Relevance
“…Such deficits during tone matching have been shown to predict higher-order impairments in working memory, reading, and emotion recognition ( 102 ). Moreover, theta band abnormalities underlying auditory MMN deficits, which have been shown to be modulated by glutamatergic NMDAR drug manipulations in schizophrenia ( 103 , 104 ), are correlated with executive functions, including working memory ( 100 , 105 ), as well as non-verbal memory and social cognition ( 100 ) in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such deficits during tone matching have been shown to predict higher-order impairments in working memory, reading, and emotion recognition ( 102 ). Moreover, theta band abnormalities underlying auditory MMN deficits, which have been shown to be modulated by glutamatergic NMDAR drug manipulations in schizophrenia ( 103 , 104 ), are correlated with executive functions, including working memory ( 100 , 105 ), as well as non-verbal memory and social cognition ( 100 ) in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Critically, theta oscillations have been implicated in synaptic plasticity (54,59,60,88,89) and in learning and memory [e.g., (63,(90)(91)(92)(93)(94)], and reduced amplitude of theta oscillations during both memory and executive function tasks have been observed in schizophrenia (95,96). Importantly, recent work in schizophrenia has mapped auditory plasticity deficits, including impaired mismatch negativity (MMN) and N100 generation during paired tone matching, to alterations in the theta frequency band (97)(98)(99)(100)(101). Such deficits during tone matching have been shown to predict higher-order impairments in working memory, reading, and emotion recognition (102).…”
Section: Discussionmentioning
confidence: 99%
“…Studies that analysed theta activity in SCZ during auditory paradigms found a significant correlation between social cognition and the theta band evoked power and phase locking values [ 96 ], and between verbal memory (but not working memory or conceptual flexibility) and theta amplitude [ 100 ]. In addition, no correlations were found between evoked theta power during an auditory oddball task and cognitive domains assessed with MCCB in FES and SCZ [ 108 ].…”
Section: Resultsmentioning
confidence: 99%
“…Discrepant findings have also been reported for associations between dMMN amplitude and cognitive functions in SCZ, FEP and CHR. Most studies reported significant correlations between lower dMMN amplitude and impairments in several cognitive domains, such as reasoning [ 184 ], problem solving [ 184 ], verbal fluency [ 166 , 182 ], verbal learning [ 115 , 169 , 186 , 187 ], vigilance [ 192 ], visual attention [ 180 , 186 , 188 ], attentional switching [ 186 ], executive functioning [ 194 ], contextual processing [ 178 ], working memory [ 96 , 115 , 166 , 179 , 191 , 193 ], speed of processing [ 169 , 180 , 189 ], non-verbal memory [ 96 ], social perception [ 195 ], social cognition [ 96 , 181 ], abstraction and thought flexibility [ 96 ], emotion affective prosody [ 183 , 195 ], as well as composite cognitive scores [ 167 , 190 ]. An innovative longitudinal machine learning study [ 90 ] carried out in FEP subjects, used a combination of clinical, functional, cognitive and several EEG indices (delta, theta and alpha event-related activity and dMMN amplitude values recorded at multiple electrodes).…”
Section: Resultsmentioning
confidence: 99%
“…Even if only a single scalp channel is of primary interest (Fz), it is recommended to use 64 channels (or more) for the application of modern signal processing techniques to remove artifacts and improve the signal to noise ratios for both scalpand source-level responses. [52][53][54][55] Using individual structural magnetic resonance imaging data rather than MNI template head models may further improve the accuracy of source dynamics in future studies.…”
Section: Discussionmentioning
confidence: 99%